Cutaneous Drug Reactions in Children Attending a Tertiary Care Hospital (TAJ: Journal of Teachers Association, 2020)
Background: Cutaneous drug reaction (CDR) is a growing health hazard in the world. Adverse drug reactions are common complications in drug therapy. About 3-8% of all hospital admissions are the results of adverse drug reactions, among them 2-3% are children and these can cause significant disability to patients. Early identification and management of adverse cutaneous drug reaction has both short term and long term prognostic significance.  Objective: To know the cutaneous reaction to drugs in children in a tertiary care hospital.  Study design: Hospital based descriptive, observational study.Subjects: 50 children with cutaneous drug reactions were studied in the department of Dermatology and Pediatric respectively in Rajshahi Medical College Hospital, Rajshahi.Methods: Data were collected by detailed history taking, physical examination and laboratory investigations in a prefixed data collection sheet and with the help of GOLD guideline after taken informed consent of the patient.Results: This study showed a significant male predominance. Male: female ratio was 1.08:1 .In this study prevalence was highest among 1-5 years age group. Cotrimoxazole, NSAIDs, anticonvulsant and quinolone were most offending medications. Maculopapular eruption, Stevens Johnson Syndrome, fixed drug eruption and urticaria were most common morphological types. Majority of CDRs were noted with oral route of administration. It was observed that almost all the CDRs that were reported involved mainly the skin. Majority of adverse cutaneous drug reactions reported were moderate in severity.Conclusion: Frequency distribution of the offending drugs and the adverse reactions revealed that adverse cutaneous drug reactions occurred mostly by cotrimoxazole, NSAIDs and quinolones. Maculopapular rash and Stevens Johnson Syndrome were the most common morphological types. A better understanding of the mechanisms underlying CRDs is important in drug development and in patient care.TAJ 2020; 33(2): 56-62